Smart home based security system for door access control using smart phone - Marrapu, Satvika; Sanakkayala, Satyanarayana; Vempalli, Arun kumar; Jayavarapu, Sai Krishna (International Journal of Engineering and Technology, 2018)
The system is regarding the remotely overseen Door availability and voice alarming with the help of Smart Phone. It captures the guest picture at the Door as Email caution. Use of Smart home security control framework became essential in our day to day life. This paper describes the outline of an advanced home security framework. In this method the door availability has been controlled based on guest character by considering the human movement location and remotely checking innovation. This paper describes the remote control framework execution and organization and allows the validated individuals in to a home as it were. This Security Framework can be implemented by using switch/calling bell and a Camera module. The camera module captures the pictures of the guest separately and ideally to make the home security framework alive on demand. In this method we used an Electromagnetic entryway bolt module which created the entryway availability. This proposed framework deploys a controller interface framework and LPC 2148. If a guest press calling bell at the door then the web Camera module is interfaced with switch to capture pictures and send these pictures as Email caution with the help of TCP/IP protocol. Now, we can control this home security system by seeing camera module video stream with the help of Smart cell Phone. Like this, the proposed home security framework allows us for sending an order as a reply of voice ready whenever the gatecrasher recognized using smart phone. By using android stage and improved JavaScript, the Clients can see the guest on the screen and able to control the entryway by locking or unlocking the door. This software can be used in a wide range of application where the physical nearness can’t be possible forever i. e in territories. The entire control framework is implemented with LPC 2148 now a days usage of smart lock system is increasing day by day in wide range of applications. This efficient effort less low power calling bell based home lock system is essential for security purpose in every home and offices. So many nations are worked on home based locking frame work to implement advanced technologies in it. Most of smart houses and business offices are associated with a chip for security purpose. Though numerous advancements take place, the clients face troubles i. e interface problems in utilizing this smart lock system. To avoid such type of issues i proposed microcontroller. This advanced home security system is useful for real time home environment.